Environs de CHATEAU-THIERRY - BELLEAU - The church (3021791159) - George Eastman House (Wikimedia Commons, 2008)
Carte postale ancienne issue de Wikimedia Commons. Titre: Environs de CHATEAU-THIERRY - BELLEAU - The church (3021791159). Accession Number: 1969:0301:0004 Maker: Bouvigny (French) Title: Environs de CHATEAU-THIERRY - BELLEAU - The church Date: 1918 Medium: collotype print Dimensions: Image: 7.5 x 12 cm Overall: 8.8 x 14 cm George Eastman House Collection General information about the George Eastman House Photography Collection is available at http://www.eastmanhouse.org/inc/collections/photography.php. For information on obtaining reproductions go to: http://www.eastmanhouse.org/flickr/index.php?pid=1977:0144:0050MP.
Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; glise; Château